International Relations in Uncommon Places - Beier, J. author. aut Link
X, 252 p.
Keywords: The central claim developed in this book is that disciplinary International Relations (IR) is identifiable as both an advanced colonial practice and a postcolonial subject. The starting problematic here issues from disciplinary IR's relative dearth of attention to indigenous peoples, their knowledges, and the distinctive ways of knowing that underwrite them. The book begins by exploring how IR has internalized many of the enabling narratives of colonialism in the Americas, evinced most tellingly in its failure to take notice of indigenous peoples. More fundamentally, IR is read as a conduit for what the author terms the 'hegemonologue' of the dominating society: a knowing hegemonic Western voice that, owing to its universalist pretensions, speaks its knowledge to the exclusion of all others.